CSR Contributions for environmental sustainability: A comparison of private banks in emerging market - Chaudhuri, Tinni; Mitra, Soham; Guha, Banhi; Biswas, Sanjib; Kumar, Pankaj (Decision Making: Applications in Management and Engineering, 2023)
Over the years corporate social responsibility (CSR) has become a source of competitive advantage for firms including banks. CSR is one of the important aspects of a private bank’s contribution to society apart from its functionality. The extant literature shows a scantiness of research concerning the assessment of the efficiency of banks in CSR expenditure towards environmental sustainability. The current work fills the gap in the literature by providing a multi-objective assessment framework to measure and compare the leading private banks based on their efficiency in CSR vis-à-vis environmental sustainability. This paper aims to study the ideal and actual contribution of the Indian private banking sector toward environmental sustainability and other sectors. This is done by using data from 10 private sector banks over 7 financial years and comparing their efficiencies over time using optimization techniques like Data Envelopment Analysis. To study the change in CSR contribution over time, the Malmquist Index has been used. City Union and HDFC have shown the highest contribution towards environmental sustainability as a part of their CSR acts consistently over the years irrespective of the income generated. The outcome of the present paper shall enable the decision-makers to formulate of the appropriate policies.